2004
DOI: 10.1093/jat/28.6.411
|View full text |Cite
|
Sign up to set email alerts
|

Deposition Characteristics of Methamphetamine and Amphetamine in Fingernail Clippings and Hair Sections

Abstract: Fingernail clippings collected from 97 consenting females, who admitted amphetamines and/or opiates use and are currently under treatment, were quantitatively analyzed for the presence of methamphetamine and amphetamine. Sixty-two subjects were found positive for methamphetamine/amphetamine. Paired nail-hair specimens were collected from 6 of these subjects for a 12-week period and analyzed to determine the duration of detectability and deposition characteristics of amphetamines in fingernails; whether data de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 13 publications
(7 reference statements)
0
30
0
1
Order By: Relevance
“…Few studies are available that specifically address the use of nails as an analytical media for the detection of drugs (188). The available studies indicate that fingernail and toenail clippings have been found as reliable as hair for the detection of methamphetamine and amphetamine in users, as these drugs are well accumulated in the nail matrix, stable in the nail, retained for a long period of time, show a good correlation with hair concentrations (174,188,189).…”
Section: Nailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies are available that specifically address the use of nails as an analytical media for the detection of drugs (188). The available studies indicate that fingernail and toenail clippings have been found as reliable as hair for the detection of methamphetamine and amphetamine in users, as these drugs are well accumulated in the nail matrix, stable in the nail, retained for a long period of time, show a good correlation with hair concentrations (174,188,189).…”
Section: Nailsmentioning
confidence: 99%
“…The available studies indicate that fingernail and toenail clippings have been found as reliable as hair for the detection of methamphetamine and amphetamine in users, as these drugs are well accumulated in the nail matrix, stable in the nail, retained for a long period of time, show a good correlation with hair concentrations (174,188,189). The mechanism of deposition at the nail matrix is complex (188,189), hence analysis of nails are considered to be a less reliable indicator of temporal trends than hair. However, analysis of nails may provide an alternate method of evaluating environmental exposures to methamphetamine.…”
Section: Nailsmentioning
confidence: 99%
“…For this reason, compounds that incorporate into hair can be detected in this sample well after they would cease to be detected in tissue, plasma and urine [115,123,127,128]. This is shown in Table 1, which summarizes (in increasing order), the timeframe of detection for drugs of abuse in selected human sample matrices.…”
Section: Principles Of Growth Exposure and Incorporation Into Human mentioning
confidence: 96%
“…Powder feathers, which grow continuously and are never molted [159], should also be investigated as potentially suitable for detecting compounds of concern. [231] b Houston [166] c Whittem et al [232] d Popot et al [140] e Tracey et al [233] f Gaillard et al [131] g Gunaratram and Wilkinson [137] h Sachs and Raff [234] i Wennig [235] j Lin et al [128] The use of any veterinary agent to augment body mass, or whose consumption poses a risk to human health (e.g., anabolic steroids, β-agonists and nitrofuran antibiotics) must be carefully monitored [168,169]. Poultry feathers are routinely monitored as part of human food safety testing procedures.…”
Section: Feathers: Growth Exposure and Incorporation With An Emphasmentioning
confidence: 99%
“…Investigations on paired hair and nail analysis for amphetamines delineated similar [16] or higher concentrations in hair [17], but one group reported slightly higher amphetamine concentrations in fingernails compared to hair [18].…”
Section: Introductionmentioning
confidence: 95%